Proximity-enhanced synthesis of DNA–peptide–DNA triblock molecules. Issue 25 (8th March 2022) - MacCulloch, Tara; Novacek, Alexandra; Stephanopoulos, Nicholas
Abstract : We report a proximity-enhanced method to synthesize a peptide flanked by two different oligonucleotide handles. Abstract : We report a proximity-enhanced method to synthesize a peptide flanked by two different oligonucleotide handles. Our method relies on sequential bioorthogonal reactions, and partial hybridization of the second handle to the first. We demonstrate the synthesis of a protease-responsive DNA "latch" and a cyclic bioactive peptide using this method.